Disability Issues in the Kinta District Community: A Review of Two Population Case Studies - Osman Ali (Asian Journal of Medicine & Health Sciences, 2022)
Royal College of Medicine Perak has been using the population case study to inculcate their students on ability to make a community diagnosis and experiencing the health intervention program. Two community case studies were selected to show the magnitude of disability in the community of Kinta District and to study the community’s perception and health practices towards this disease. It was shown that the awareness about the presence of disabled people in the community was considered low (42.8%). The community perceived that disabled people had suffered from a social exclusion, discrimination and mistreatment from the family and a society (71.7%). Physical disabilities were quite common, especially among the elderly in the community. Half of the older adults in the community suffered from bone and joint pain (50.9%). The knowledge on bone and joint pain were fair among respondents (67.1%). Much older person, females and having been diagnosed for the symptom seem to have better knowledge and attitude as compared to the opposite. In conclusion, there is a need to increase awareness among the public about the presence of disabled people (PWDs) around them and to provide a moral, economic, and social support to them. Discrimination and social exclusion should be stopped or minimized. Knowledge and attitude of PWDs should be strengthened to face the challenges of the future. Skill trainings, medications, rehabilitation equipment and social support should be offered or given to PWDs to increase their mobility and independence living.